HEP together with wind farm WEP : simulation of energy generation and water level in the reservoir - Strak, Karol (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri This thesis presents model to simulate energy generation from combined wind – hydro power system. Together with hydropower plant, wind farm is to be built in Iceland. For this reason two hypothetical facilities were considered as a case study. One of them was the hydropower plant at the Hólmsá River with the reservoir at Atley located in the south of Iceland. The other hypothetical facility was the wind farm located also in the south of Iceland, Vatnsfell. Both locations were analyzed in order of available energy resources. Trend of typical hydrological and meteorological year for both water discharge and wind speed differed. During winter discharge was greater than during summer. Opposite situation was noted in case of mean wind speed. This difference allows for complementing seasonal niches and increase of firm power generation during simultaneous operation of the system. It was concluded that with greater number of wind turbines installed, efficiency factor due to friction losses increases and average water turbine efficiency drops. This was caused by lower discharge through the water turbine when more wind power was installed. For investigated number of turbines the highest performance of the system was when 6 to 16 MW of wind power was installed. In simulation the main focus was on firm energy. Different years and examination of high – low water discharge and high – low wind speed for energy generation was done. Yearly energy generation for hydropower site between high and low discharge year differed more than 40%. Energy generation from wind between high and low wind speed differed less than 10%. In the end, energy generation and water level in the reservoir from the combined wind – hydro system were presented. As a part of this research analyses of possibilities to apply designed simulation model to Polish conditions were investigated. European Economical Area Grant